1986
DOI: 10.1136/vr.119.16.401
|View full text |Cite
|
Sign up to set email alerts
|

A study of the justification for intensive tick control in Kenyan rangelands

Abstract: Sixty male weaner cattle at the National Range Research Station, Kiboko, Kenya were placed in four groups of 15 animals under four different tick control regimens for 16 months. The treatment groups were: spraying with acaricide weekly, spraying every three weeks, spraying whenever group mean tick infestations reached more than 200 per animal (once only in the course of the study) and a control unsprayed group. The cattle were weighed monthly. There were no significant differences between the liveweight gains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Reduction in tick populations may be achieved by the "long-interval tick control m e t h o d " or by treatment only during the high tick season (Tatchell et al, 1986). Reduction in tick populations may be achieved by the "long-interval tick control m e t h o d " or by treatment only during the high tick season (Tatchell et al, 1986).…”
Section: E L I M I N a T I O N O F T I C K Smentioning
confidence: 99%
“…Reduction in tick populations may be achieved by the "long-interval tick control m e t h o d " or by treatment only during the high tick season (Tatchell et al, 1986). Reduction in tick populations may be achieved by the "long-interval tick control m e t h o d " or by treatment only during the high tick season (Tatchell et al, 1986).…”
Section: E L I M I N a T I O N O F T I C K Smentioning
confidence: 99%
“…Management costs would increase the financial burden to the point where there could be no conceivable benefit from intensive tick control. This has been seen elsewhere in Africa (Tatchell et a/., 1986) wherever cattle are immune to TBD, and the only putative benefit to be gained from tick control is in reducing specific tick damage.…”
Section: Discussionmentioning
confidence: 89%
“…Studies carried out by Kayaa (2000) have also revealed that synthetic dewormers slow the decomposition of manure. The annual cost for importing acaricides has been estimated at US$9.3 million in Zimbabwe (Perry et al, 1990), US$16 million in Kenya (Tatchell et al, 1986), US$10 million in Zambia (Pegram et al, 1988), US$26 million in Tanzania (Kagaruki, 1997) and Uganda (OkelloMarandure 1837…”
Section: Limitations Of Orthodox Livestock Health Care Practicesmentioning
confidence: 99%